2017
DOI: 10.1158/1538-7445.am2017-5253
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 5253: Arctigenin inhibits prostate tumor growth in vitro and in vivo in obese state

Abstract: Arctigenin is a novel anti-inflammatory lignan derived mainly from the seeds of Arctium lappa which is an herb widely used in traditional Chinese medicine to treat inflammation related diseases. We previously demonstrated that arctigenin strongly inhibited prostate tumor cell growth in cell culture and mouse models in non-obese state. The present study investigated the tumor inhibitory effect of arctigenin in obese state. An in vitro obese setting was created by co-culture of mouse adipocytes 3T3-L1 with andro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Furthermore, arctigenin has been reported to increase the chemosensitivity of several cancer cells, including HepG2, HeLa and K562( 12 ). Arctigenin has also been applied to the treatment of various types of cancer, and the anti-tumor function has been illustrated in various cancers, including gallbladder cancer ( 13 ), human retinoblastoma cells ( 14 ), lung cancer ( 15 ) and prostate tumor ( 16 ). Wang et al ( 17 ) reported that arctigenin could trigger autophagy, induce apoptosis and enhance the sensitivity of colorectal cancer cell to chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, arctigenin has been reported to increase the chemosensitivity of several cancer cells, including HepG2, HeLa and K562( 12 ). Arctigenin has also been applied to the treatment of various types of cancer, and the anti-tumor function has been illustrated in various cancers, including gallbladder cancer ( 13 ), human retinoblastoma cells ( 14 ), lung cancer ( 15 ) and prostate tumor ( 16 ). Wang et al ( 17 ) reported that arctigenin could trigger autophagy, induce apoptosis and enhance the sensitivity of colorectal cancer cell to chemotherapy.…”
Section: Introductionmentioning
confidence: 99%